Earnings, Cash Flow and Accrual Characteristics of the SET 50 Companies During the COVID-19 Pandemic - Narktabtee, Kanogporn; Jarungidanan, Preecha (NIDA Business Journal, 2022)
This study examines earnings, cash flow and accrual characteristics of the SET 50 companies during the COVID-19 pandemic. The study examines earnings persistence and one-year ahead cash flow predictability of these accounting information during the year 2018-2021, covering the COVID-19 Pandemic. The results show that in the year 2020 earnings has relative low persistence when compared with the earnings from the prior years, and accruals has lowest persistence in three years, and has lower persistence than cash flows. Also, earnings 2020 has lowest explanatory power in one-year ahead cash flows. During three-year analysis, cash flows is dominant information in explaining future cash flows, while accruals do not have incremental explanatory power beyond cash flows in explaining future cash flows. The evidences reveal the usefulness of earnings, cash flows, and accruals in predicting the companies’ performance during the unusual situation.